PENGARUH INTERAKSI PACLOBUTRAZOL DAN TIPE TANAM JAJAR LEGOWO PADA PRODUKSI PADI METODE TANAM SRI - Christiane M. Tambajong; Edy ., Lengkong; David S. Runtunuwu (AGRI-SOSIOEKONOMI, 2016)
This study aims to find the effect of interaction of paclobutrazol and type Legowo Row Planting in paddy fields that use SRI cultivation method to increase rice yield, and can determine the best combination of effective and can be applied in paddy fields to increase production. The research was conducted in the Village of Sulu, Tatapaan Sub-district, South Minahasa Regency. This study uses a field experiment with split plot design in groups of two factors. As the first factor is the type of Legowo Row Planting 2: 1 and 4: 1. The second factor is the provision of paclobutrazol by spraying the plants with a dose of: 0 ppm and 600 ppm. Paclobutrazol will be given only once, that when plants in active vegetative growth period (about 30 days old plants after transplanting). Data analysis was used Two-Factor Interactions calculation. The interaction of two factors occured, if the effect of a factor changes when the change level of other factors change. The results indicated that the existence of interaction between treatment paclobutrazol and Legowo row that high interaction in the inhibition of the vegetative growth of rice crops varieties Serayu, middle interactions on the rate of plant growth, middle interactions in the treatment of paclobutrazol and Legowo row to increase the content of chlorophyll a and chlorophyll b in the leaves, the influence of high interaction of the number of productive tillers, high interaction on panicle length, high interaction to the increased weight of 1,000 grains, high interaction of the increase in the weight of dry unhusked rice per plot, and the lack of interaction to increase the number of grains per panicle. Paclobutrazol 600 ppm treatment gave a positive response on Legowo row 2: 1 for the inhibition of vegetative growth of crops to prevent crop is too high and not easily fall, increased chlorophyll a, increasing the weight of 1,000 grains and increased the weight of milled rice per plot. Paclobutrazol 600 ppm treatment gave a positive response on Legowo row 4: 1 to increase the pace of growth, increased chlorophyll b, an increase in the number of productive tiller and panicle length.